The Influence Of Financial Attitudes And Financial Self Efficacy On The Personal Financial Management Of Krupuk Industry Employees In Tulangan District - Muhammad Nur Hidayat Sukarman; Jeziano Rizkita Boyas (Yayasan Pendidikan Riset dan Pengembangan Intelektual (YRPI), 2025)
This study aims to examine how financial attitudes and financial self-efficacy influence the personal financial management of employees of the cracker industry in Tulanagan district. The following study is a quantitative quantitative study with a descriptive approach. 158 respondents were taken by purposive sampling from a population of 203 employees. Variables were measured using a Likert scale with a weight range of 1 to 5. Data analysis was carried out by applying Partial Least Square (PLS). The study findings indicate that: (1) financial attitudes have a positive impact on personal financial management (2) financial self-efficacy has a positive impact on personal financial management, (3) financial attitudes and financial self-efficacy simultaneously influence personal financial management.